2016
DOI: 10.1371/journal.pone.0158465
|View full text |Cite
|
Sign up to set email alerts
|

Coupling between Theta Oscillations and Cognitive Control Network during Cross-Modal Visual and Auditory Attention: Supramodal vs Modality-Specific Mechanisms

Abstract: Cortical theta band oscillations (4–8 Hz) in EEG signals have been shown to be important for a variety of different cognitive control operations in visual attention paradigms. However the synchronization source of these signals as defined by fMRI BOLD activity and the extent to which theta oscillations play a role in multimodal attention remains unknown. Here we investigated the extent to which cross-modal visual and auditory attention impacts theta oscillations. Using a simultaneous EEG-fMRI paradigm, healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 48 publications
(49 reference statements)
4
14
0
Order By: Relevance
“…Nonetheless the existence of a well known crossmodal interaction during cognitive processing has also been reported [52]- [57], hypothesizing the key role of supramodal regions [58], it should be borne in mind that visual and acoustic signals are basically processed in different and anatomically separated sensory specific areas. Regarding the present results, it might be hypothesized that lighting could influence only those areas involved in modality specific processing for visual stimuli and not those specialized for acoustic ones and for supramodal activity.…”
Section: Discussionmentioning
confidence: 88%
“…Nonetheless the existence of a well known crossmodal interaction during cognitive processing has also been reported [52]- [57], hypothesizing the key role of supramodal regions [58], it should be borne in mind that visual and acoustic signals are basically processed in different and anatomically separated sensory specific areas. Regarding the present results, it might be hypothesized that lighting could influence only those areas involved in modality specific processing for visual stimuli and not those specialized for acoustic ones and for supramodal activity.…”
Section: Discussionmentioning
confidence: 88%
“…hippocampus), by increasing and decreasing the firing rate probability of single neurons subjected to the extracellular local field potentials induced by more global cortical oscillations [28,29]. In the context of attention, theta oscillations have been found in cross-modal paradigms involving visual and auditory attention [30,31]. These authors showed that theta allows fronto-parietal top-down modulation of visual and auditory cortices during cross-modal attention.…”
Section: Discussionmentioning
confidence: 99%
“…Theta synchrony is suggested to be induced into the cortex via the hippocampal‐cortical pathway (Klimesch, ; Ekstrom et al ., ). In the literature, increased theta synchrony has been associated with cognitive processes such as memory (Klimesch et al ., , ), multimodal interaction and attention (Wang et al ., ), spatial awareness both with and without visual and self‐motion cues (Kahana et al ., ; Ekstrom et al ., ; Landau et al ., ; Vass et al ., ) as well as with sensory–motor interaction (Zarka et al ., ; Bland & Oddie, for a review), predictive timing of movement (Arnal & Giraud Mamessier, for a review) and emotional processing (Krause et al ., ; Balconi & Lucchiari, ; Knyazev et al ., ). Interestingly, theta synchrony did not differ between groups during Dance or Stick Figure.…”
Section: Discussionmentioning
confidence: 99%
“…Alpha and beta bands have been associated with motor processes (Pineda, ; Pavlidou et al ., ; Hobson & Bishop, ), whereas the theta band, and its coupling to gamma band, is linked to several cognitive and affective functions (Krause et al ., ; Kahana, ; Canolty & Knight, ). In addition, both theta and alpha bands are modified during attentional and multimodal processing (Mathewson et al ., ; van Driel et al ., ; Wang et al ., ).…”
Section: Introductionmentioning
confidence: 97%